Effects of Blue Light on Puberty and Ovary in Female Rats - Aylin Kılınç Uğurlu; Aysun Bideci; Mürşide Ayşe Demirel; Gülnur Take Kaplanoğlu; Duygu Dayanır; Özlem Gülbahar; Tuba Saadet Deveci Bulut; Esra Döğer; Mahmut Orhun Çamurdan (Galenos Yayincilik, 2023)
INTRODUCTION: This study was designed to examine the effect of blue light exposure and exposure time on puberty in an animal model. METHODS: Eighteen 21-day-old female Sprague Dawley rats were divided into three equal groups which were: control group (CG); blue light-6 hours (BL-6); and blue light-12 hours (BL-12). CG rats were maintained with 12/12-hour light-dark cycles. The animals in BL-6 and BL-12 were exposed to blue light of wavelength 450-470 nm and intensity of 0.03 uW/cm2 for 6 and 12 hours, respectively. Exposure to blue light continued until the first signs of puberty. Serum follicle stimulating hormone (FSH), luteinizing hormone (LH), estradiol, testosterone, dehydroepiandrosterone sulfate (DHEA-S), leptin and melatonin were measured. Subsequently the ovaries and uterus were examined histomorphologically. RESULTS: The median day of puberty start was 38, 32 and 30 for the CG, BL-6, and BL-12 groups, respectively (p=0.001). FSH, testosterone, DHEA-S, and leptin concentrations of all groups were similar. However, LH and estradiol concentrations in BL-6 were higher compared to CG (p=0.02). There was a negative correlation between blue light exposure, exposure time, and melatonin concentrations (r=-0.537, p=0.048). Ovarian tissue was compatible with puberty in all groups. As blue light exposure time increased, capillary dilatation and edema in the ovarian tissue increased. Prolonged exposure was associated with polycystic ovary-like (PCO) morphological changes and apoptosis in granulosa cells. DISCUSSION AND CONCLUSION: These results suggest that exposure to blue light and the duration of exposure induced earlier puberty in female rats. As the duration of blue light exposure increased, PCO-like inflammation, and apoptosis were detected in the ovaries.